(untitled) (European Journal of Pure and Applied Mathematics, 2025)
In this work, the direct product of Q-algebras is discussed. We investigate some properties of this direct product related to concepts of subalgebra, ideal, and G-part of Q-algebras. We obtain that the set G-part of the direct product of Q-algebras is an exactly the direct product of sets G-part of Q-algebras. We also provide the characterization of two elements subsets of the direct product of Q-algebras to be subalgebras. Moreover, we show the connection between the direct product of Q-algebras and CI-algebras.